The Influence of Knowledge Sharing and Competency on Organizational Citizenship Behavior With the Mediation of Organizational Commitment - Sahadizah, Yamaudina; Rijanti, Tristiana (AFEBI Management and Business Review, 2024)
This study examines the impact of knowledge sharing and competency on organizational citizenship behavior (OCB), with organizational commitment as a potential mediating variable, within the Regional Civil Service Agency (BKD) of Central Java Province. Recognizing the challenges of suboptimal OCB and low organizational commitment among employees, this research seeks to identify key drivers to enhance voluntary performance beyond formal job requirements. Using purposive sampling, 88 employees with a minimum Diploma-III education and three years of experience were selected for analysis. Data were collected through questionnaires and analyzed using multiple linear regression. The results reveal that knowledge sharing positively and significantly influences organizational commitment but does not directly affect OCB. Conversely, competency positively and significantly impacts OCB but does not influence organizational commitment. Furthermore, organizational commitment does not mediate the relationship between knowledge sharing, competency, and OCB. These findings offer practical insights for public sector organizations seeking to foster OCB through strategic focus on employee competency development and collaborative knowledge-sharing practices. Future research is encouraged to explore additional mediators and contextual factors influencing OCB in public institutions. Keywords: Knowledge Sharing, Competency, Organizational Citizenship Behavior (OCB), Organizational Commitment, Public Sector Management